2017
DOI: 10.3389/fmicb.2017.00237
|View full text |Cite
|
Sign up to set email alerts
|

Association Mapping Reveals Genetic Loci Associated with Important Agronomic Traits in Lentinula edodes, Shiitake Mushroom

Abstract: Association mapping is a robust approach for the detection of quantitative trait loci (QTLs). Here, by genotyping 297 genome-wide molecular markers of 89 Lentinula edodes cultivars in China, the genetic diversity, population structure and genetic loci associated with 11 agronomic traits were examined. A total of 873 alleles were detected in the tested strains with a mean of 2.939 alleles per locus, and the Shannon's information index was 0.734. Population structure analysis revealed two robustly differentiated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Sixty L. edodes strains from wild and cultivation strains [32,33] were used to screen thermotolerance in this study by primarily observing the mycelial recovery. The well-grown mycelial plugs were inoculated into sawdust plates (78 g of hardwood sawdust, 20 g of wheat bran, 2 g of lime and 20 g of agar in 1 L of distilled water).…”
Section: Mushroom Strains Growth Conditions and Thermotolerance Assaymentioning
confidence: 99%
“…Sixty L. edodes strains from wild and cultivation strains [32,33] were used to screen thermotolerance in this study by primarily observing the mycelial recovery. The well-grown mycelial plugs were inoculated into sawdust plates (78 g of hardwood sawdust, 20 g of wheat bran, 2 g of lime and 20 g of agar in 1 L of distilled water).…”
Section: Mushroom Strains Growth Conditions and Thermotolerance Assaymentioning
confidence: 99%
“…For edible mushrooms, pileus expansion leads to the loss of nutrition and the decline of economic value. According to edible mushroom marketing and sales standards, the pileus size and shape are significant agronomic traits and among the most important indexes for product quality [3]. Therefore, it is critical to control pileus expansion during fruiting management of commercially cultivated edible fungus.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, H E , H O , and PIC values of the cultivars were higher than those of the wild strains. In several recent studies, the analysis of 88 wild strains showed H E of 0.44, H O of 0.29, and PIC of 0.31 using two SSRs and 68 InDels [13], and the analysis of 89 cultivars revealed H E of 0.46, H O of 0.55, and PIC value of 0.38 using 48 SSRs and 249 InDels [36]. Studies conducted in Korea and China have shown that the genetic diversity of L. edodes was also higher in the cultivars than in the wild strains.…”
Section: Discussionmentioning
confidence: 97%